1993
DOI: 10.21273/hortsci.28.9.885
|View full text |Cite
|
Sign up to set email alerts
|

Plant Spacing Influences Watermelon Yield and Yield Components

Abstract: Watermelon [Citrullus lanatus (Thunb.) Matsum & Nakai] cultivars StarBrite and Crimson Sweet were grown during 1991 and 1992 in rows 1.5 m apart at plant spacings of 0.9, 1.5, or 2.2 m. Total fruit yield, marketable fruit yield, fruit-weight distribution, and estimated gross returns were determined for each spacing treatment. Total and marketable fruit yields were greater overall for `StarBrite' than for `Crimson Sweet'. Except for 1991 `Crimson Sweet' yields, marketable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 7 publications
(3 reference statements)
4
29
0
1
Order By: Relevance
“…Increased number of fruit more than compensated for decreasing fruit weight and resulted in an overall increase in yield. In a similar study with watermelon (Citrullus lanatus), it was concluded that the yield component contributing most to increased yields was increased fruit count per unit land area (NeSmith, 1993).Watermelon is another vine crop where recommended plant populations vary widely depending on the state or source of the recommendation. Texas recommends a plant population for commercial triploid watermelon production of 2180 to 3350 plants/acre (5387-8278 plants/ha) (Daniello, 1996), whereas Florida recommends about 1450 to 1740 plants/acre (3583 to 4299 plants/ha).…”
mentioning
confidence: 99%
“…Increased number of fruit more than compensated for decreasing fruit weight and resulted in an overall increase in yield. In a similar study with watermelon (Citrullus lanatus), it was concluded that the yield component contributing most to increased yields was increased fruit count per unit land area (NeSmith, 1993).Watermelon is another vine crop where recommended plant populations vary widely depending on the state or source of the recommendation. Texas recommends a plant population for commercial triploid watermelon production of 2180 to 3350 plants/acre (5387-8278 plants/ha) (Daniello, 1996), whereas Florida recommends about 1450 to 1740 plants/acre (3583 to 4299 plants/ha).…”
mentioning
confidence: 99%
“…In cucurbit crops the effects of plant density on fruit yield and fruit quality are well documented. In watermelon the marketable yield was increased by decreasing the in-row spacing from 2.2 to 0.9 m (NeSmith, 1993), or by decreasing the space between rows from 4.5 to 1.5 m and that between the plants in the row from 2.4 to 0.6 m (Brinen et al, 1979). In summer squash, high plant densities of between 3 and 6 plants/m 2 produced the highest total and marketable yields in both sandy soil in Florida (Dweikat and Kostewicz, 1989) and heavy soil in Israel (Paris et al, 1986).…”
mentioning
confidence: 99%
“…In Georgia, marketable fruit yields increased by 29% to 34% as plant density increased from 3000 to 7410 plants/ha. In that study, plant density did not affect fruit size, but the number of fruits per unit area increased as plant density increased (NeSmith, 1993). In Oklahoma, total marketable yield increased linearly by 60% as the density increased from 1000 to 9000 plants / ha (Duthie et al, 1999).…”
Section: Resultsmentioning
confidence: 64%